Pengembangan Media Collage Photo Frame dengan Menggunakan Model Kooperatif Learning pada Pembelajaran IPA Siswa Kelas IV SD Negeri 36 Kota Lubuklinggau - Mardiana, Elza; Erwandi, Rudi; Firduansyah, Dedy (LP4MK STKIP PGRI Lubuklinggau, 2024)
This development aims to develop collage photo frame media using a cooperative learning model in science learning for class IV students at SD Negeri 36 Lubuklinggau City. Testing the validity, practicality and effectiveness of collage photo frame media using the cooperative learning model in science learning for fourth grade students at SD Negeri 36 Lubuklinggau City. The type of research used is Research and Development with the ADDIE development model. The subjects of this research were fourth grade students at SD Negeri 36 Lubuklinggau City. Data collection techniques use observation, interviews, questionnaires and tests. Based on the results of the validity analysis of collage photo frame media in science learning for fourth grade students at SD Negeri 36 Lubuklinggau City using Aikens V, a language validation assessment of 0.83% was obtained, a media validator of 0.78%, and a material validator of 0.94%. Analysis of teacher and student practicality assessment sheets shows that the collage photo frame media using the cooperative learning model in science learning meets the very practical criteria with an average score of 85%. Then analysis of the effectiveness assessment obtained an average N-Gain score of 0.71% in the high category. Based on the research results, it can be concluded that the collage photo frame media using the cooperative learning model in science learning has proven to be valid, practical and effective so it is suitable for use in the fourth grade learning process at SD Negeri 36 Lubuklinggau City.